1962
DOI: 10.1121/1.1937026
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Studies of Aqueous Solutions of Non-electrolytes

Abstract: Absorption measurements were made in the ranges 1.5 to 230 Mc/sec and 0° to 45°C at various concentrations. Diethylamine solutions showed single-relaxation behavior, attributed to complex formation by hydrogen bonding. Absorption attributed to separation of phases near the lower critical solution temperature was shown in addition by triethylamine solutions. In methyl diethylamine solutions (L.C.S.T.=49°C), the transition from single- to double-relaxation behavior arising from these 2 mechanisms was observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…0.2, than for those observed in water + methanol. It is noteworthy that the first of these extrema (and the only one for [C0(3Mepy)~Cl~] +) occurs at a mol fraction of propan-2-01 which corresponds closely with that where the sharp minimum in % -V, O occurs [12], and the second extremum for [Co(3Etpy),Clz]+ occurs at about the same mol fraction of propan-2-01 as where the maximum in the ultrasonic absorption occurs [14]. As these extrema in the physical properties are usually taken to indicate situations where sharp changes occur in the solvent structure, with the lower x 2 probably indicating where the maximum struc- ture formation has been induced [20] within the Frank-type "ice-bergs" of structured water sulting probably in the onset of the breakdown of the structure of the "icebergs" [20], these correlations support the suggestion that changes in solvent structure influence the rates of solvolysis.…”
Section: Variation Of the Transition State Parameters With Solvent Comentioning
confidence: 75%
See 1 more Smart Citation
“…0.2, than for those observed in water + methanol. It is noteworthy that the first of these extrema (and the only one for [C0(3Mepy)~Cl~] +) occurs at a mol fraction of propan-2-01 which corresponds closely with that where the sharp minimum in % -V, O occurs [12], and the second extremum for [Co(3Etpy),Clz]+ occurs at about the same mol fraction of propan-2-01 as where the maximum in the ultrasonic absorption occurs [14]. As these extrema in the physical properties are usually taken to indicate situations where sharp changes occur in the solvent structure, with the lower x 2 probably indicating where the maximum struc- ture formation has been induced [20] within the Frank-type "ice-bergs" of structured water sulting probably in the onset of the breakdown of the structure of the "icebergs" [20], these correlations support the suggestion that changes in solvent structure influence the rates of solvolysis.…”
Section: Variation Of the Transition State Parameters With Solvent Comentioning
confidence: 75%
“…0.04 [12], the positive structural contribution to the change in the temperature of the maximum density of water with the addition of propan-2-01 El31 and the maximum in the ultrasonic absorption at x 2 ca. 0.18 [14], all suggest that additions of propan-2-01 to water, whilst maintaining water-rich conditions, induce the formation of structure in the solvent. The variation of the rate constants and the transition state parameters with solvent composition for the solvolysis of these complexes in water + propan-2-01 will be compared with similar variations in water + methanol [8] where the above indicators Ell-151 suggest that less structure is formed in water when methanol is added.…”
mentioning
confidence: 94%
“…clathrate-like) structures. In contrary, Baumgartner and Atkinson [9] relate the formation of such stuctures to the minima of the compressibility isotherms, while according to Andreae et al [10] the compressibility minimum can be explained in terms of solute-solvent complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent circuit is shown in Figure 1, and expressions for the total capacity as a function of frequency are easily obtained in tenns of the sample and electrodes resistivity and capacity . 10 o It is also known 36 that the resistivity of the protein powder decreases exponentially with increasing hydration. 3 6 Using the above quoted expressions it can be shown that for this very reason the total capacity must increase abruptly at a critical value of the hydration.…”
Section: H-bonded Moleculesmentioning
confidence: 99%